Chemopreventive Action of Compounds from Parmelia Perlata (Global Journal of Science Frontier Research, 2020)
Cancer prevention may be accomplished by phytochemicals obtained from vegetables, fruits, spices, teas, herbs and medicinal plants. The investigations on the species of Parmelia proved to be source of unique chemical agents that have already been proved to be effective against various types of cancer. Present study focus on chemopreventive activity against random-bred male Swiss albino mice through oral administration of dried ethanolic extract of traditional medicinal lichen Parmelia perlata. Further ethanolic extract of entitled lichen afforded three novel compounds.
Keywords: Cancer; Parmelia Perlata; Ethanolic Extract; LPO; SOD